1993
DOI: 10.1016/0014-5793(93)80357-z
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen induces collagenase expression in human skin fibroblasts

Abstract: Singlet oxygen generated in a dark reaction by thermodissociation of an endoperoxide (NDPOJ elicits an increase in mRNA of interstitial collagenase (MMP-1) in cultured human fibroblasts. The effect is enhanced in deuterium oxide-based medium and is abolished in the presence of non-toxic doses of sodium azide. In contrast, the mRNA level of the tissue inhibitor of metalloproteinases (TIMP-1) remains unaltered under these experimental conditions. These observations support the suggestion that an unbalanced synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 20 publications
2
71
0
4
Order By: Relevance
“…Evidence from several studies has indicated that photoaging and also intrinsic skin aging coincides with visible changes in the skin which are the results of collagen polymerization and degradation. These effects are also elicited by 1 O 2 , which is generated in vivo under exposure to UVA and is known to mediate the UVA-induced enhancement of MMP-1 expression in the dermal layer of the skin (54,56). In our hands exposure of up to 60 J/cm 2 of UVA irradiation changes the expression levels of MMP-1 mRNA and TIMP-1 mRNA (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Evidence from several studies has indicated that photoaging and also intrinsic skin aging coincides with visible changes in the skin which are the results of collagen polymerization and degradation. These effects are also elicited by 1 O 2 , which is generated in vivo under exposure to UVA and is known to mediate the UVA-induced enhancement of MMP-1 expression in the dermal layer of the skin (54,56). In our hands exposure of up to 60 J/cm 2 of UVA irradiation changes the expression levels of MMP-1 mRNA and TIMP-1 mRNA (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Taking into account 1 O 2 formation after UVA irradiation (23,25,54), we tested for a role of singlet oxygen in UVAinduced proteasome inhibition employing NaN 3 as a singlet oxygen quencher. Results suggest that 1 O 2 is indeed a mediator of UVA-induced proteasome inhibition in fibroblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…UVA regulates the expression of various genes including heme oxygenase-1, matrix metalloproteinase-1, IL-1a/b, IL-6, intracellular adhesion molecule, STAT3, AP-1 and AP-2 (Basu- Modak and Tyrrell, 1993;Grether-Beck et al, 1996;Klotz et al, 1999;Maziere et al, 2001;Scharffetter-Kochanek et al, 1993;Wlaschek et al, 1997;Zhang et al, 2001b;Silvers and Bowden, 2002). Considerable work is currently underway to elucidate the signal transduction mechanisms that are induced by UVA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on fibroblast or keratinocyte cultures revealed that through the generation of oxidative species (Tyrell and Keyse, 1990), UVA induces a decrease in Epidermal Growth Factor (EGF) binding (Djavaheri-Mergny et al, 1994), a modification of phospholipid metabolism (Hanson and deLeo, 1990) and lipid peroxidation (Morlie Á re et al, 1991;Moysan et al, 1995). In addition, UVA also leads to the production of extracellular degrading enzymes, stromelysin 1 and interstitial collagenase (Petersen et al, 1995;Sawamura et al, 1996;Scharffetter et al, 1991Scharffetter et al, , 1993Wlaschek et al, 1994Wlaschek et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%